A new lowland forest Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodactylus) from Ranong Province, peninsular Thailand - Sumontha, Montri; Pauwels, Olivier S. G.; Panitvong, Nonn; Kunya, Kirati; Grismer, L. Lee (Zootaxa, 2015)
We describe a new lowland forest-dwelling Cyrtodactylus from Suk Samran District, Ranong Province, southern peninsular Thailand, having a blotched dorsal pattern, a continuous series of poreless enlarged femoral and precloacal scales, 18–20 regularly arranged dorsal tubercle rows, no precloacal groove, no transversely enlarged subcaudal plates and a maximal known snout-vent length of 59.6 mm. Cyrtodactylus ranongensis sp. nov. seems closely related to C. quadrivirgatus, but is readily distinguished from it by having 35–40 ventral scale rows, a reddish iris, heavy dorsal mottling, and lacking longitudinal dark-brown elements in its dorsal pattern.